Recurrent water deficit causes epigenetic and hormonal changes in citrus plants. Issue 1 (December 2017) - Neves, Diana; Almeida, Lucas; Santana-Vieira, Dayse; Freschi, Luciano; Ferreira, Claudia; Soares Filho, Walter; Costa, Marcio; Micheli, Fabienne; Coelho Filho, Maurício; Gesteira, Abelmon
Abstract The present study evaluated the physiological, molecular and hormonal parameters from scion/rootstock interaction of citrus plants during recurrent water deficit. Responses of the Valencia (VO) scion variety grafted on two rootstocks with different soil water extraction capacities, Rangpur Lime (RL) and Sunki Maravilha (SM), during three successive periods of water deficit: plants exposed to a single episode of water deficit (WD1) and plants exposed to two (WD2) and three (WD3) recurrent periods of WD were compared. The combinations VO/RL and VO/SM presented polymorphic alterations of epigenetic marks and hormonal (i .e . abscisic acid, auxins and salicylicacid) profiles, which were particularly prominent when VO/SM plantswere exposed toWD3 treatment. Upon successive drought events, the VO/SM combination presented acclimatization characteristics that enable higher tolerance to water deficit by increasing transpiration (E ), stomatal conductance (g s ) and photosynthetic rate (A ), which in turn may have facilitated the whole plant survival. Besides providing comprehensive data on the scion/rootstock interactions upon successive stress events, this study brings the first dataset suggesting that epigenetic alterations in citrus plants triggered by recurrent water deficit lead to improved drought tolerance in this crop species.